Use of the Magellan Robotic System for Conventional Transarterial Chemoembolization (cTACE): A 6-Patient Case Series Showing Safety and Technical Success - Clements, Warren; Scicchitano, Madeleine; Koukounaras, Jim; Joseph, Tim; Goh, Gerard S. (Journal of Clinical Interventional Radiology ISVIR, 2019)
Robotic endovascular technology is an emerging concept, and is being developed to allow more precise navigation of anatomy in challenging endovascular cases. The Magellan Endovascular System allows either direct or remote steerability of a 2-point articulating robotic platform with the ability to place a conventional microcatheter through the catheter tip. Such flexibility may help to reach an otherwise difficult anatomic location, especially in variant anatomy. To date, this platform has been shown to be technically successful in a small number of different settings. This case series shows another potential platform for such technology and explores the technical use and overall safety in conventional transarterial chemoembolization (cTACE). The study retrospectively assessed 6 patients undergoing selective cTACE. Treatments were performed in a single center by two experienced interventional radiologists. Fluoroscopy time, radiation dose, anatomic target, and adverse events were logged. In spite of a longer than expected average fluoroscopy time, which can be expected for a first-generation technology, the average radiation dose was comparable to literature and technical success was able to be shown in all 6 patients with no adverse events. This technology has wide scope for future use and once overcoming a learning curve, may allow us to avoid repeat procedure attempts thus reducing fluoroscopy time and leading to earlier successful treatment. Providing a platform of interest and usability in the interventional radiology world may also lead to further development of smaller, cheaper, and more widely-accessible devices.
Keywords: TACE; chemoembolization; magellan; robot; robotic; endovascular; novel